STORTELLING TO FACILITATE ELEMENTARY SCHOOL STUDENTS IN IMPROVING SPEAKING SKILLS IN LEARNING ENGLISH AS A FOREIGN LANGUAGE (EFL) - Simorangkir, Imelda Malawaty (Journal of Community Research and Service, 2021)
Because the skills of speaking English as a foreign language (EFL) in Indonesia are still concern and less than maximal, even becoming a phenomenon to date. This study choose storytelling as a learning techniques to facilitate students to increase speaking skills in English learning. So, this study aims to see the success of storytelling techniques in learning foreign languages, and increased skills to speak English students at the grades 6 elementary school. There is an average value (mean score) of student learning outcomes of each aspect are as follows: vocabulary aspects of 17.5, the aspect of pronunciation of 17.3, aspects of smoothness of 16.7, aspects of the structure of 16.7, and the meaning aspects of 17.9. Of the overall average value on every aspect, students can be said to almost reach the highest score, namely 20 on the assessment criteria for each aspect. The findings of this study showed storytelling is a technique that is worthy of being used as a technique or approach to foreign language learning. The storytelling can spur students' interest in talking The storytelling managed to facilitate students to increase speaking skills in learning English as a foreign language (EFL).,Students also provide a good response to this storytelling activity. Then, there is the increase in the speaking skills of elementary school students achieve very satisfactory value, which is 40% of students get a score of 97 for the highest value, and only 10% with a score of 62 for the lowest value. This study uses a direct method in storytelling activities. For data collection, this study uses qualitative and quantitative methods for data analysis.